BIBLIOGRAFI BERANOTASI TENTANG SITUS KERATON RATU BOKO - Rangkuti, Nurhadi (BRIN, 2003)
The site of the Ratu Boko Palace, which is located on a hillside in the Prambanan area, Yogyakarta, is an archaeological relic of the Old Mataram Kingdom (8-10 century AD). The temple complex consists of three groups of buildings, namely (1) the western part, which is a three-story courtyard. The three pages are connected by closed gates (paduraksa). On these courtyards there are remains of buildings that have now been restored, (2) Southeastern part, in the form of a group of buildings consisting of two parts. One part is a stone floor with a stone fence. This building is called the